2016
DOI: 10.1007/s13555-016-0138-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Non-Antibiotic Treatments for Patients with Acne: A Review

Abstract: Acne is a very common non-infectious skin condition that is frequently treated in dermatological practices. Because acne is often chronic and may persist for years, safe and effective long-term maintenance therapy is often required. Given the increasing frequency of antibiotic-resistant bacteria and the gravity of the consequences of this trend, it behooves dermatologists to maximize use of non-antimicrobial therapy when treating acne. In this review of the literature we present data regarding the efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 107 publications
0
43
0
8
Order By: Relevance
“…At the same time, P. acnes colonizes the pilosebaceous duct, triggering the release of inflammatory mediators into the surrounding tissue and a response by immunocompetent cells, further contributing to the development of comedones . Acne most often occurs in the face, neck, back, and chest, all areas with many pilosebaceous units …”
Section: Pathogenesis Of Acnementioning
confidence: 99%
See 3 more Smart Citations
“…At the same time, P. acnes colonizes the pilosebaceous duct, triggering the release of inflammatory mediators into the surrounding tissue and a response by immunocompetent cells, further contributing to the development of comedones . Acne most often occurs in the face, neck, back, and chest, all areas with many pilosebaceous units …”
Section: Pathogenesis Of Acnementioning
confidence: 99%
“…This assertion is supported by the work of Jain and Ahmed, who showed that pretreatment of skin with adapalene enhanced the penetration of topical clindamycin phosphate, thus increasing the efficacy of the antibiotic. Tretinoin, adapalene, and tazarotene are the only retinoids approved for use in the USA . Topical retinoids used alone are an excellent therapy for the treatment of predominantly comedonal acne …”
Section: Treatment Of Acnementioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly applied non‐pharmacological therapies are laser and light‐based therapies, chemical peels, microneedling, (micro)dermabrasion and (mechanical) lesion removal. Non‐pharmacological therapies are applied as independent therapies, in combination with conventional therapies or as maintenance therapy, especially in more persistent or chronic types of acne where long‐term therapy is required . However, sufficient evidence‐based support in the efficacy and safety of non‐pharmacological therapies is scarce.…”
Section: Introductionmentioning
confidence: 99%